Whole Plastome Sequences of Two Drug‐Type Cannabis: Insights Into the Use of Plastid in Forensic Analyses. Issue 1 (14th August 2019) - Matielo, Cristiane Barbosa D'Oliveira; Lemos, Rafael Plá Matielo; Sarzi, Deise Schröder; Machado, Lilian de Oliveira; Beise, Dalvan Carlos; Dobbler, Priscila Caroline Thiago; Castro, Renata Machado; Fett, Mauro Sander; Roesch, Luiz Fernando Würdig; Camargo, Flávio Anastácio de Oliveira; Stefenon, Valdir Marcos
Abstract: DNA is one of the fastest growing tools in forensic sciences, increasing reliability in forensic reports and judgments. The use of DNA has increased in different areas of the forensic sciences, such as investigation of plant species, where plastid DNA has been used to elucidate and generate evidence in cases of traceability of genetically modified and controlled plants. Even with several advances and the practice of using DNA in forensic investigations, there are just few studies related to the identification of genetic tools for the characterization of drug and nondrug‐types of Cannabis . Herein, the whole plastomes of two drug‐type Cannabis are presented and have their structures compared with other Cannabis plastomes deposited in the GenBank, focusing in the forensic use of plastome sequences. The plastomes of Cannabis sativa "Brazuka" and of the hybrid Cannabis AK Royal Automatic presented general structure that does not differs from the reported for other C. sativa cultivars. A phylogenomic analyses grouped C. sativa "Brazuka" with the nondrug C. sativa cultivars, while the hybrid Cannabis AK Royal Automatic placed isolated, basal to this group. This suggests that the analysis of plastomes is useful toward genetic identification of hybrids in relation to C. sativa .